A fourteen-component high-entropy alloy@oxide bifunctional electrocatalyst with a record-low ΔE of 0.61 V for highly reversible Zn–air batteries. Issue 41 (2nd September 2022) - Jin, Zeyu; Zhou, Xuyan; Hu, Yixuan; Tang, Xiaowei; Hu, Kailong; Reddy, Kolan Madhav; Lin, Xi; Qiu, Hua-Jun
Abstract : Nanostructured high-entropy materials such as alloys, oxides, etc., are attracting extensive attention because of their widely tunable surface electronic structure/catalytic activity through mixing different elements in one system. Abstract : Nanostructured high-entropy materials such as alloys, oxides, etc., are attracting extensive attention because of their widely tunable surface electronic structure/catalytic activity through mixing different elements in one system. To further tune the catalytic performance and multifunctionality, the designed fabrication of multicomponent high-entropy nanocomposites such as high-entropy alloy@high-entropy oxides (HEA@HEO) should be very promising. In this work, we design a two-step alloying–dealloying strategy to synthesize ultra-small HEA nanoclusters (∼2 nm) loaded on nanoporous HEO nanowires, and the compositions of both the HEA and HEO can be adjusted separately. To demonstrate this concept, a seven-component HEA (PtPdAuAgCuIrRu) clusters@seven-component HEO (AlNiCoFeCrMoTi)3 O4 was prepared, which is highly active for both oxygen evolution and reduction reactions. Our comprehensive experimental results and first-principles density functional theory (DFT) calculations clearly show that better oxygen evolution reaction (OER) performance is obtained by optimizing the composition of the HEO support, and the seven-component HEA nanocluster is much more active for the ORR when compared with pure Pt due to the modified surface electronic structure. Specifically, the high-entropy composite exhibits an OER activity comparable to the best reported value, and the ORR activity exceeded the performance of commercial Pt/C in alkaline solutions with a record-low bifunctional Δ E of 0.61 V in 0.1 M KOH solution. This work shows an important route to prepare complex HEA@HEO nanocomposites with tuned catalytic performance for multifunctional catalysis and energy conversion.